BIOACTIVE COMPOUNDS AND YIELD OF RED SEAWEED (Eucheuma cottonii)) EXCTRACT - Hotmeriah Padang; Mery Sukmiwati; Andarini Diharmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT             Eucheuma cottonii  is one of algae that able to live on seawater and one of the biggest part of sea plantation. Tthis research was aimed to determine  bioactive compounds and yield of red seaweed extract (Eucheuma cottonii) from Jang village, Moro region, Tanjung Balai Karimun district. Research method was extracted red seaweed Eucheuma cottonii with using methanol solution. The analysis parameter was bioactive compound (phytochemical) and yield. Result analysis showed that from phytochemical test bioactive compound of Eucheuma cottonii extract was flavonoid, steroid and saponin. The yield extract was 2.22% Keyword: Eucheuma cottonii, extract, phytochemical, yield